Extracting reusable document components for variable data printing - Bagley, Steven R.; Brailsford, David F.; Ollis, James A. (2007)
Variable Data Printing (VDP) has brought new flexibility and dynamism to the printed page. Each printed instance of a specific class of document can now have different degrees of customized content within the document template.